Avaliação do serviço PAEFI por meio do estudo da rede de apoio social e afetiva de crianças vítimas de abuso sexual - Nascimento, Danielly Bart do (2011)
The present study aims to evaluate the effectiveness of the Service for Protection and Specialized Assistance to families and individuals (PAEFI) Program as part of the social and affective support network, from the viewpoint of both the assisted children and the professionals who assist them. It is hoped that the research can provide data which may foster public policies as well as the practices of those involved in programs which deal with this type of audience. Two children (a boy and a girl of ten and eleven years old respectively), their parents, the social assistant and the psychologist who assisted them in the PAEFI participated in the research. Data were collected by means of interviews, analysis of records, application of the Five Field Map, observations and field diaries. The observations were facilitated by the Ecological Insertion method whereas the Bioecological Model for human development was applied for the discussion of results. Results indicated that the program was perceived by the girl as part of the social and emotional support network, but not by the boy. This difference may be due to the way children perceived and dealt with the environment, and to the type of relationship established. It was also evidenced that factors related to the structure of the program have hampered its performance. Therefore, the study indicated the need for more investments in the PAEFI s infrastructure from the physical environment to the training of those professionals who are part of it.